Rosai–Dorfman disease of the central nervous system: A clinical, radiological, and prognostic study of 12 cases - Zhang, Xingshu; Yin, Wen; Guo, Youwei; He, Yi; Jiang, Zhipeng; Li, Yuzhe; Xie, Bo; Zhang, Seng; Jiang, Xingjun; Liu, Qing; Yuan, Jian (Frontiers in Oncology, 2022)
Background: Rosai-Dorfman disease (RDD) is a rare benign non-Langerhans cell histiocytic proliferative disease. RDD with central nervous system (CNS) involvement (CNS-RDD) is extremely rare. Its etiology is unclear and there are no consensus recommendations for its treatment. More studies are needed to elucidate the clinical and radiological manifestations and prognosis of CNS-RDD. Methods: From January 2012 to June 2022, 12 patients with CNS-RDD (intracranial or spinal) were retrospectively analyzed, including collecting clinical data, imaging data and pathological findings, summarizing imaging characteristics, and conducting follow-up studies on CND-RDD patient treatment and prognosis. Results: Twelve CNS- RDD patients (9 males and 3 females, aged 12-67 years) were enrolled in this study. Nine patients represented convex and/or skull base RDD (8 with edema, 6 with lobulation and/or pseudopodium sign, 4 with multiple intracranial lesions), two patients had parenchymal RDD, and 1 patient had spinal cord subdural lesions. Symptoms of patients would vary according to locations of the lesion, including but not limited to headache, dizziness, seizure, cranial nerve dysfunction, and visual impairment. The immunohistochemistry of RDD showed positive expression of S100 and CD68, but not CD1a. Total resection (n = 7), subtotal resection (n = 3), partial resection (n = 1), stereotaxic biopsy (n = 1) were achieved respectively. Combination of chemotherapy plus steroid therapy was performed on two patients (relapsing case and residual lesion) and showed remarkable effect. Conclusion: CNS-RDD, as a rare disease, is a great challenge for clinicians to make accurate diagnosis. Solitary CNS-RDD are easily misdiagnosed as meningioma. However, when the MRI imaging of the disease represent dura-based masses with significant edema, homogeneous enhancement, lobulation and/or pseudopodium sign, we should consider it might be the CNS-RDD. Surgery is the most effective therapy for CNS-RDD, while steroids and chemotherapy are relatively safe and effective for the postoperative treatment of relapsing cases or residual lesions.